Video Game Play Does Not Improve Spatial Skills When Controlling for Speed-Accuracy Trade-Off: Evidence From Mental-Rotation and Mental-Folding Tasks. Issue 3 (June 2022) - Safaei, Ali; Rahmanian, Mahdieh; Oraki, Mohammad; Zinchenko, Artyom
Researchers have been divided on the efficacy of computerized cognitive training (CCT) for enhancing spatial abilities, transfer of training, and improving malleability of skills. In this study, we assessed the effects of puzzle video game training on subsequent mental rotation (MR) and mental folding (MF) performance among adults with no cognitive impairment. We assessed participants at baseline with the Shepard-Metzler MR test followed by the differential aptitude test: space relations MF test (i.e., far transfer). We ranked participants' skills on these pre-tests and used a matching technique to form two skill groups from which we then randomly assigned members of each skill group either to an experimental group or a wait-list control group. The experimental group played two puzzle video games closely related to two-dimensional and three-dimensional MR tasks during 4-week training sessions (total of 12 hour of video games). Post-training, participants completed the MR and MF tests again. Two months later, we re-assessed only the experimental group's spatial skills to explore the sustainability of the trained performance. In addition to response times (RT) and error scores (ES), reported separately, we combined these variables into rate correct scores (RCS) to form an integrated measure of potential speed-accuracy trade-offs (SAT). As a result, we did not find significant improvements in MR performance from CCT engagement, nor did participants show a transfer of skills obtained by practicing MR-related puzzle games to a MF task. Based on the current findings, we urge caution when proposing a game-based intervention as a training tool to enhance spatial abilities. We argue that separately interpreting individual test measures can be misleading, as they only partially represent performance. In contrast, composite scores illuminate underlying cognitive strategies and best determine whether an observed improvement is attributable to enhanced capacities or individual heuristics and learned cognitive shortcuts.